2013
DOI: 10.1007/s12160-013-9559-6
|View full text |Cite
|
Sign up to set email alerts
|

Depression Treatment Enhances Adherence to Antiretroviral Therapy: a Meta-Analysis

Abstract: BACKGROUND Depression is a risk factor for nonadherence to HIV/AIDS treatment. PURPOSE A meta-analysis was conducted to examine whether treatment of depression and psychological distress improves antiretroviral therapy adherence. METHODS PubMed and PsycINFO databases were systematically searched for relevant articles. Studies that reported an association between depression treatment (or an intervention with a component addressing mental health) and antiretroviral adherence were included. RESULTS Across 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
164
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(174 citation statements)
references
References 61 publications
7
164
0
3
Order By: Relevance
“…Depression is known to have adverse effects on HIV-related outcomes, for example there is a substantial evidence base that depression reduces adherence to anti-retroviral medication (ART) (Sin & DiMatteo, 2014). Potentially related to reduced adherence, a study which followed up women 6-8 years after birth reported that women with depression were significantly more likely to have an increased rate of disease progression (hazard ratio, HR ¼1.61; 95% CI ¼ 1.28-2.03) and 2-fold increased risk of death (HR ¼2.65; 95% CI ¼ 1.89-3.71) (Bing et al, 2001).…”
Section: Ipv Hiv and Mental Health Burden In Africamentioning
confidence: 99%
“…Depression is known to have adverse effects on HIV-related outcomes, for example there is a substantial evidence base that depression reduces adherence to anti-retroviral medication (ART) (Sin & DiMatteo, 2014). Potentially related to reduced adherence, a study which followed up women 6-8 years after birth reported that women with depression were significantly more likely to have an increased rate of disease progression (hazard ratio, HR ¼1.61; 95% CI ¼ 1.28-2.03) and 2-fold increased risk of death (HR ¼2.65; 95% CI ¼ 1.89-3.71) (Bing et al, 2001).…”
Section: Ipv Hiv and Mental Health Burden In Africamentioning
confidence: 99%
“…21 Given the above, it is critical from a public and individual perspective to investigate and describe the interventions that are effective in improving adherence to ART. Systematic reviews report that there is limited evidence on interventions to improve adherence to ART in the pediatric population; 22 yet older adults are less likely to be non-adherent; 23 there may be benefit in addressing mental health issues that affect adherence; 5,24,25 motivational interviewing may offer some benefit, 26 and reduce viral load in youth. 27 Weekly reminder text messages [28][29][30] and treatment supporters 29 also improve adherence and reduce viral load in low resource settings.…”
Section: Introductionmentioning
confidence: 99%
“…(10) Some authors present a high prevalence of depression in PLHA, exerting a significant impact in the development of diseases and being registered as one of the main causes of suicide and psychiatric appointments. (6) Despite the high depression rates identified in this population, however, knowledge gaps about depression remain among PLHA in low and middle-income countries. (4) And the difference in the depressive symptoms of men and women living with HIV in Brazil according to the BDI domains is not understood yet, which made it difficult to compare these results with other studies developed in the country.…”
Section: Discussionmentioning
confidence: 98%
“…(4) In PLHA, it is known for being negatively associated with worse compliance with antiretroviral treatment, (5) therapeutic outcomes and risk behaviors, (6) besides its considerable impact in the treatment and social relationships (7) and in the more rapid progression to Aids and death. (1) Hence, the importance of measuring and understanding the influence of depression in this population is highlighted.…”
Section: Introductionmentioning
confidence: 99%